2019
DOI: 10.1016/j.joms.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maxillomandibular Advancement Surgery on Pharyngeal Airway Volume and Polysomnography Data in Obstructive Sleep Apnea Patients

Abstract: To study volumetric changes in the upper airway in obstructive sleep apnea (OSA) patients after maxillomandibular advancement (MMA) and compare findings to polysomnography (PSG) data of the same patients. Patients and Methods Study consisted of 20 OSA patients (mean age 48 years, range 31-59 years, 1 female, 19 male). Mean SNB and SNA angles before surgery indicated mandibular and maxillary retrognathia. All were treated with MMA including pre-and post-operative orthodontics. Pre-and post-treatment cone-beam c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Apenas cinco dos nove estudos trouxeram os valores do IAH pós-operatório satisfatórios, sendo em média de oito eventos por hora [1][2][3][4]6 deve ser menor que 20 eventos por hora com redução de 50% no pós-operatório 6 . Nesse sentido, a maioria dos estudos incluídos nesta revisão mostrou uma redução significativa nos valores médios do IAH pós-operatório em relação ao IAH préoperatório, relatando uma taxa de sucesso de 65 a 100% 1-3,6,14-17 .…”
Section: Resultados E Discussõesunclassified
See 2 more Smart Citations
“…Apenas cinco dos nove estudos trouxeram os valores do IAH pós-operatório satisfatórios, sendo em média de oito eventos por hora [1][2][3][4]6 deve ser menor que 20 eventos por hora com redução de 50% no pós-operatório 6 . Nesse sentido, a maioria dos estudos incluídos nesta revisão mostrou uma redução significativa nos valores médios do IAH pós-operatório em relação ao IAH préoperatório, relatando uma taxa de sucesso de 65 a 100% 1-3,6,14-17 .…”
Section: Resultados E Discussõesunclassified
“…dispositivos de avanço mandibular e terapia com pressão positiva contínua nas vias aéreas (CPAP) são atualmente as opções de tratamento mais conservadoras e visam o avanço mandibular para aumentar a permeabilidade da via aérea 1,[3][4]6 .…”
unclassified
See 1 more Smart Citation
“…With regard to the maxillary advancement, multiple studies have found no correlation between degree of maxillary advancement and a reduction in AHI [ 35 , 36 ]. Increased airway volume following MMA has been considered to be necessary for improving OSA [ 28 , 37 ], while Chang et al reported that there was a plateau effect for the airway volume increase as a result of maxillary advancement [ 38 ]. In addition to the potential predictors mentioned above, some other factors of interest to clinicians were also investigated in terms of predicting MMA outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mandibular advancement surgeries are very well indicated for patients with sleep apnea and airway problems. In addition, patients with mandibular retrognathism generally present reduced airway volume, and a recent study 25 demonstrated that after the surgical procedure, an average increase of 64% was possible. Therefore, more studies with Early Benefit approaches in patients with skeletal Class II and mandibular retrognathism would be of extreme importance.…”
Section: Discussionmentioning
confidence: 99%